Pemanfaatan Pangan Lokal Sawi Laut Untuk Meningkatkan Sifat Organoleptik Dan Kadar Serat Nugget Tahu - Devi, Anisa Rahma; Wiqayatun , Khazanah (JURNAL SVASTA HARENA RAFFLESIA, 2024)
Nugget is one of the fast food products, which is a product made from seasoned ground meat, then covered with flour adhesive, breadcrumb coating, then fried and can be served immediately or frozen for longer storage. Processing tofu into nuggets is one alternative with a lower econimical value and also has a high nutritional value of protein. Most processed nugget products have a weakness in low fiber content, with the addition of local food sea mustard in nuggets will increase fiber content because vegetables are a source of food fiber. Sea mustard (Launaea Sarmentosa L.) is a vegetable that is proven to have fiber content, besides that sea mustard also has polyphenol and flavonoid compounds, alkaloid content, carbohydrates, amino acids, steroids, glycosides and many more that are beneficial to the body and have an important role in maintaining health. This research method is experimental research with a completely randomized design (CRD) with three treatments and three repetitions. The variables of this study were organoleptic test and fiber content test. The results of variance analysis found that the color with the highest average value of 3.86 (rather like), on the roma with an average value of 3.76 (rather like), on the texture with an average value of 3.62 (rather like), on the taste of the average value of 3.74 (rather like) and on the fiber test with an average value of 4.56. Thus it can be concluded that tofu nuggets with the addition of sea mustard have a significant effect on color and fiber content, while aroma, texture, and taste have no significant effect on tofu nuggets.